Diet and Metabolic Dysfunction Clinical Evidence - Gaetano Santulli (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The purpose of these books is to have an updated systematic overview examining, in detail, the functional role of different diets and dietary components in maintaining glucose homeostasis and preventing long-term complications. The first book includes experimental evidence from preclinical research, whereas the second book provides studies in the clinical scenario.